Campūrāmāyaṇam - Bhojarāja, King of Malwa, 11th cent (Saṃvāda Jñānaratnākarākhyayantre, 1885)
On the life and exploits of Rāma (Hindu deity); includes Vātadūta with autocommentary by Krṣṇanātha Nyāyapañcānana Bhaṭṭācāryya.